Primary Needle-Knife Fistulotomy Versus Conventional Cannulation Method in a High-Risk Cohort of Post-Endoscopic Retrograde Cholangiopancreatography Pancreatitis. (7th January 2020) - Jang, Sung Ill; Kim, Dong Uk; Cho, Jae Hee; Jeong, Seok; Park, Jin-Seok; Lee, Don Haeng; Kwon, Chang-Il; Koh, Dong Hee; Park, Se Woo; Lee, Tae Hoon; Lee, Hye Sun
Abstract : OBJECTIVES: Successful biliary cannulation is a prerequisite and important component of endoscopic retrograde cholangiopancreatography, but conventional cannulation methods (CCMs) have a postendoscopic retrograde cholangiopancreatography pancreatitis (PEP) rate of 14.1% in patients at high risk for PEP. The aim of this study was to evaluate the effectiveness and safety of needle-knife fistulotomy (NKF), compared with a CCM, when used for primary biliary access in patients at high risk for developing PEP. METHODS: A total of 207 patients with one or more risk factors for PEP were prospectively enrolled. The patients were randomly allocated to one of 2 groups according to the primary biliary cannulation technique (NKF or CCM). We compared biliary cannulation success rates, cannulation and procedure times, and the incidence of adverse events, including PEP, between the groups. RESULTS: The mean number of PEP risk factors was similar between the groups (NKF, 2.2 ± 1.0; CCM, 2.2 ± 0.9). PEP occurred in 8 patients in the CCM group and in no patients in the NKF group (9.2% vs 0%, P < 0.001). The rates of other adverse events did not differ between the groups. The biliary cannulation success rate was high in the NKF group, but relatively low in the CCM group, possibly because of the stringent failure criteria aimed at reducing PEP. However, the mean cannulation and total procedural times were longer in the NKF group than in the CCM group. DISCUSSION: NKF is an effective and safe procedure to gain primary biliary access in patients at high risk for developing PEP. ClinicalTrials.gov, NCT02916199.